Clinico-Pathological study of carcinoma breast in a tertiary care hospital from West Bengal, India: A Cross-Sectional Observational study - Sahoo, Deepak Kumar; Nandi, Mintu Mohan; Basu, Srijan; Chatterjee, Sanjay; Das, Amit Kumar (Asian Journal of Medical Sciences, 2021)
Background: Breast cancer is one of the most common cancer in women. BC represents a heterogeneous group of tumors that are diverse in behavior, outcome, and response to therapy. Aims and Objective: The present study was undertaken to assess various clinical parameters and to evaluate correlation with histo-pathological grading in breast carcinoma patients. Materials and Methods: The study was conducted in the Surgical outpatient department and Indoor surgical wards of Deben Mahato Sadar Hospital (DMSH), Purulia, West Bengal from July, 2019 to December, 2020. 104 patients with diagnosis of BC aged between 20 years to 80 years were selected. Results: Among 104 patients, 41.3% patients were in the group of 41-50years. This study revealed that the patient had mostly IDC i.e. 78.8% and had triple negative BC (51.9%). Association of HPE vs. Stage, subtypes vs stage and Tru-cut biopsy vs HPE were statistically significant. Conclusion: The study showed that breast cancer tends to present in middle aged women and positively correlate with the present markers of bad prognosis.